Mini review on the design of axial type eddy current braking technology - Waloyo, H.T.; Ubaidillah, Ubaidillah; Tjahjana, D.D.D.P.; Nizam, M.; Koga, T. (Institute of Advanced Engineering and Science, 2019)
Eddy Current Brake (ECB) is a type of electric braking that uses eddy current to produce braking forces. This article delivers a solid review of the design of Axial ECB, which is very promising for an alternative braking system. Several types of axial ECB are classified and named as a single disk, double disk, and unipolar model. The classification of axial ECB is based on the design of coil placement, which induces axial area of the disk as well as the electromagnet source. A potential issue for the development of axial ECB is also discussed to explore the braking performance improvement of the axial type ECB. It was highlighted that research on how to change the direction of magnetic field vectors by changing the shape of the pole-shoe on the electromagnetic ECB in axial type has not been widely studied. Therefore, this issue would be interesting for future investigation.